Spiritually Oriented Couple,_x000D_ Marriage and Family Therapies - EKŞİ, HALİL (My University, 2020)
In this review, it is aimed to focus on the integration of spirituality into familyoriented psychological help processes. To conceptualize the reflection of spiritualityon the family system more clearly and to make sense of the spirituality-familyrelationship, the issue of spirituality was examined in specific processes such as inthe relationship between parents and children, between spouses and in the transitionprocess from adolescence to late age. The paradoxical nature of spirituality in familyrelationships was emphasized. For this purpose, spirituality was discussed both asa source of problems and as a source for solutions in family relations. Spirituallyoriented psychological clinical help is an emerging field in Turkey. Seeing thatspirituality is such an important issue in family relations and marriage, it is aimed tobring a family-focused approach to the spiritually oriented psychological help process.So, by addressing ethical issues, this review aims to offer a new perspective to fieldpractitioners working with couples and families in clinical practice.

Bu çalışmada, maneviyat konusunun aile odaklı psikolojik yardım süreçlerine entegre_x000D_ edilmesine odaklanılmıştır. Maneviyatın aile sistemine yansımasını daha net bir_x000D_ şekilde kavramsallaştırabilmek ve maneviyat-aile ilişkisini anlamlandırabilmek için_x000D_ bu konu ebeveyn-çocuk ilişkisi, eşler arası ilişki, yaşlılık dönemine geçiş gibi spesifik_x000D_ süreçler içerisinde incelenmiştir. Maneviyatın, bu süreçlerdeki paradoksal doğası_x000D_ vurgulanmış ve maneviyat konusu hem sorunların kaynağı olabilme hem de sorunlara_x000D_ çözüm olabilme özelliğiyle tartışılmıştır. Manevi yönelimli psikolojik danışma ve_x000D_ terapi Türkiye’de son zamanlarda çalışılan, güncel bir alandır. Maneviyatın, aile ve_x000D_ evlilik ilişkilerindeki önemi göz önünde bulundurularak, bu bölümde manevi yönelimli_x000D_ psikolojik yardım süreçlerinde, aile odaklı bir yaklaşımın tanıtılması hedeflenmiştir._x000D_ Bu nedenle, etik konulara değinilerek, klinik uygulamada çiftler ve ailelerle çalışan_x000D_ alan uygulayıcılarına yeni bir bakış açısının sunulması amaçlanmıştır.
Manevi Yönelimli Çift, Evlilik ve Aile Terapiler